Near-infrared oximetry of the brain - Madsen, Per Lav; Secher, Niels H (Progress in neurobiology, 1999)
Near-infrared (IR) light easily penetrates biological tissue, and the information offered by in vivo spectroscopy of cerebral oxygenation is detailed and comes with a high temporal resolution. Near-IR light spectroscopy (NIRS) reflects cerebral oxygenation during arterial hypotension, hypoxic hypoxaemia and hypo- and hypercapnia. As determined by dual-wavelength NIRS, the cerebral O2 saturation integrates the arterial O2 content and the cerebral perfusion, and as established for skeletal muscle, NIRS obtains information on tissue oxygenation and metabolism beyond that obtained by venous blood sampling. Caveats of cerebral NIRS include insufficient light shielding, optode displacement and a sample volume including muscle or the frontal sinus mucous membrane. The relative influence from the extracranial tissue is minimized by optode separation and correction for an extracranial sample volume, or both. The natural pigment melatonin and also water are of little influence to spectroscopic analysis of cerebral oxygenation, whereas bilirubin systematically lowers ScO2 and attenuates the detection of changes in cerebral oxygenation. By NIRS, reduction of cytochrome oxidase is demonstrated during hypoxic hypoxaemia and head-up tilt-induced arterial hypotension, but the changes are small. In the clinical setting, NIRS offers useful information in patients with both systemic and local cerebral circulatory impairment, for example, during cranial trauma, surgery on the cerebral arteries, orthostasis and acute heart failure. Whereas mapping of the brain circulation is needed for jugular venous sampling to reflect either global or local oxygenation, the determination of cerebral oxygenation by NIRS has the advantage of localized monitoring of the cerebral cortex.